Asthma in children. Issue 1 (January 2017) - Daines, Luke; McMurray, Ann
Asthma affects 1 100 000 children in the UK and is thus the most common long-term condition of childhood. The prevalence of childhood asthma symptoms in the UK is among the highest worldwide and this contributes to the estimated £1 billion annual cost of asthma care to the NHS. Children still die from asthma despite advances in its management, and mortality rates have changed very little over the past 20 years. The recent national review of asthma deaths provided a stark reminder of 'why asthma still kills' and made key recommendations for children with asthma. However, evidence-based recommendations are still poorly implemented. This article seeks to enthuse the next generation of GPs to prioritise the improvement of asthma care in children.